Cladosporin Derivatives Obtained by Biotransformation Provide Guidance for the Focused Derivatization of this Antimalarial Lead Compound. (11th December 2018) - Fredenhagen, Andreas; Schroer, Kirsten; Schröder, Harald; Hoepfner, Dominic; Ligibel, Mathieu; Porchet Zemp, Liliane; Radoch, Caroline; Freund, Ernst; Meishammer, Aldo
Abstract: Cladosporin, a natural product known for decades, has recently been discovered to display potent and selective antiplasmodial activity by inhibition of lysyl‐tRNA synthetase. It was subjected to a panel of oxidative biotransformations with one fungal and two actinomycetes strains, as well as a triple mutant bacterial CYP102A1, yielding eight, mostly hydroxylated, derivatives. These new compounds covered a wide chemical space and contained two pairs of epimers in the tetrahydropyran ring. Although less potent than the parent compound, all analogues showed activity in a cell‐based synthetase assay, thus demonstrating uptake and on‐target activity in living cells with varying degrees of selectivity for the enzyme lysyl‐tRNA synthetase from Plasmodium falciparum and highlighting sites suitable for synthesis of future cladosporin analogues. Compounds with adjacent hydroxy functions showed different MS/MS fragmentation that can be explained in terms of an, in some cases, regioselective loss of water followed by a retro‐Diels–Alder reaction. Abstract : Late‐stage functionalization by biotransformation gave eight derivatives of the antimalarial lead compound cladosporin. These products displayed various degrees of selectivity for the enzyme lysyl‐tRNA synthetase from P. falciparum and highlighted sites suitable for synthesis of future cladosporin analogues.